Eficácia de um programa de educação alimentar e nutricional para o aumento do consumo de hortaliças e frutas por escolares - Nasser, Leila Adnan [UNIFESP] (2010)
Objective: Evaluate the effectiveness of a food and nutrition educational program in the increase of the consumption of vegetables by school children. Methods: This is a longitudinal randomized controlled study performed in 280 (two hundred and eighty) children, of both genders, aged between 11 (eleven) and 12 (twelve) years old, students of 03 (three) fundamental education schools of São Paulo city, from February to September 2007. At first, all students answered the Food Frequency Questionnaire (FFQ) and than were divided randomly in two different groups: intervention and control group. After that, the intervention group was submitted to a Food and Nutritional Education Program based on ludo pedagogical activities. After 05 (five) months, the Food Frequency Questionnaire (FFQ) was applied again, in order to verify the effectiveness of the food and nutritional education program in increasing the consumption of vegetables. Results: It was observed that in the interventional group, an increase of the consumption of vegetables was significantly bigger than in the control group, indicating that the ludo pedagogical activities may have influenced the children’s eating habit in a positive way. In the control group there were no significant changes. Regarding school children that didn’t have the habit of consuming vegetables, it was observed that in the intervention group the introduction of the consumption of different kinds of vegetable (chard/cabbage, beet, avocado, papaya, mango and strawberry), was greater then in the control group, indicating that the educational intervention method may also have influenced this change. Conclusion: The food and nutrition education based on ludo pedagogical activities is effective in relation to vegetables, both for increasing the previously consumed amount and for the acceptance of different vegetables by school children.